Buried rigid pipe-soil interaction in dense and medium sand backfills under downward relative movement: 2D finite element analysis. (December 2019) - Qin, Xiaogang; Ni, Pengpeng; Du, Yan-Jun
Abstract: The downward resistance between pipes and soils dominates the serviceability and structural integrity of buried rigid pipelines when geohazard conditions such as ground subsidence and normal faults are encountered. This study first presented a numerical investigation on the interaction between buried rigid pipes and soils under downward relative movements, based on which a novel mathematical representation of the bearing force-displacement curve was derived. Sand backfills in the numerical model were characterized using plane-strain shear strength parameters, and the increment of elastic modulus with depth was accounted. Simulated results showed that the bearing resistance kept increasing with the relative displacement and the failure resistance was analogous to the local shear, rather than the general shear bearing capacity. The proposed force-displacement relationship consisted of a nonlinear region before the mobilization of failure resistance and a linear post-failure region. The rationality of proposed method was evaluated against experimental measurements reported in published studies and calculations from the commonly used method, which can provide a basis for assessing performance of buried rigid pipes under downward relative movement conditions.